Characterisation of mortars from Tróia Archaeological Site - Esteves, A. (2010)
This paper presents results obtained in the European project PRODOMEA (PROject on high compatibility technologies and systems for conservation and DOcumentation of masonry works in archaeological sites in the MEditerranean Area). The aim of the project was to create a new approach for assessment of the compatibility of conservation treatments on masonry architectural assets and elements present in Roman age archaeological sites in the Mediterranean Basin. This paper presents the characterization procedure applied to the Roman mortars employed in the archaeological site of Tróia, Portugal, one of the project case-studies. The characterization procedure and results are presented and discussed.